Uncovering the Dimensions to Increase Islamic Job Satisfaction in Socially Nuanced Economic Institutions - Wijiharta; Wening, Nur (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to explore the dimensions of Islamic Job Satisfaction that will be useful to increase Islamic job satisfaction in socially nuanced economic institutions. Samples were taken from employees of Islamic Microfinance Institutions (IMFI, LKMS, KSSPS BMT) at convenience. Data collection from 30 respondents using a questionnaire instrument was then analyzed using quantitative descriptive methods. The results showed that Islamic Job Satisfaction achieved a very high score for employees of social economic institutions (KSPPS, BMT) was very high (4,088 or 81.76%). The spiritual dimension of Islamic Job Satisfaction received the highest rating (4,386 or 87.72%), while the economic dimension received the lowest rating (3,908 or 78.16%). Future research suggestions take respondents from other socially nuanced economic institutions (educational institutions, health institutions) or other institutions (economic, governmental, social)